VAKSINASI COVID 19 DAN KEBIJAKAN NEGARA : PERSPEKTIF EKONOMI POLITIK - Idil Akbar (Universitas Jenderal Ahmad Yani, 2021)
This study aims to explain how the political economy perspective views the functions of the state and government in the Covid 19 vaccination plan. Currently, Indonesia is trying to overcome the COVID-19 pandemic by entering into contracts to purchase covid 19 vaccines with three vaccine producers from China, namely Cansino, G42 . / Sinopharm and SinoVac. The hope is that the Covid 19 outbreak can be handled immediately to restore the economy and citizens. This study uses Caporaso and Levine's political economy theory, especially in looking at the relationship between power and state mechanisms against the market, so that it will be seen whether the state and the government are carrying out their functions as part of the new solution or problem behind the covid 19 vaccination. analytic descriptive. Data were analysed using the stages of organizing data, reading and recording, as well as descriptions, clarifications, and interpretations.